Connecting : harnessing your emotions to enhance your creativity - Larocca, Paulina, ....-; Ibbotson, Tony, ....- (Amsterdam : BIS Publishers, 2019)
Connecting is an homage to our creative forces. Each page is an illustrative example designed to enlighten, illuminate, challenge and provoke. You can start anywhere, dip in and out or read it end to end.
Keywords: Creativity